Qiraah science learning to enhance the religious competence of Al-Qur'an of Islamic Education students - Amirotul Khasanah; Khodijatul Kubro; Fahmi Hadianto (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
This study aims to describe the process and results of qiraah science learning to improve the religious competence of the Al-Qur'an of Islamic Education (PAI) students of UIN Sunan Kalijaga Yogyakarta. This type of research is qualitative with field and descriptive research patterns. Data collection techniques are through observation, questionnaires, interviews, and documentation. The subjects of this research are students of the PAI study program at UIN Sunan Kalijaga class of 2021/2022 and lecturers teaching Living Al-Qur'an and Hadith courses. The data that has been collected is analyzed using data triangulation. The results of the study show that learning qiraah science with the lecture method, the Jibril practice method, and the discussion method is considered quite effective in improving the religious competence of Al-Qur'an in the form of pronunciation of the letters of Al-Qur'an with various sanad versions. Learning qiraah science uses the reference of Manba'ul Barakat Fi Sab'a al-Qiraat by K.H. Ahsin Sakho Muhammad with Whatsapp digital media. The obstacles faced include limited space and time, lack of learning media, and lack of understanding of tajweed and student motivation. Nevertheless, all respondents said that learning Qiraat Science is essential, and this knowledge's benefits can be felt in understanding everything related to Al-Qur'an. Recommendations that arise from the results of this study are the need to increase learning time and facilities, as well as the utilization of more innovative digital technology to support the learning process of qiraah science so that it can more effectively improve the religious competence of PAI students of UIN Sunan Kalijaga.